Effect of polyester fiber on compressive strength and split tensile strength properties of high strength concrete - Mohsin Ali; Aneel Kumar; Samar Hussain Rizvi; Naraindas Bheel (Mehran University Research Journal of Engineering and Technology)
High strength concrete (HSC) is essential for large-scale projects, such as bridges, dams, and high-rise buildings, as it allows for reduced dimensions of beams and columns. This experimental study investigates the effect of polyester fiber on the compressive and split tensile strength properties of HSC grade C60. A total of 90 concrete mixes were prepared, incorporating polyester fiber at varying volumes of 0%, 0.2%, 0.3%, 0.4%, and 0.5%, with curing periods ranging from 3 to 28 days. The results demonstrate that the inclusion of polyester fiber significantly enhances the mechanical properties of HSC, with optimal compressive strength achieved at 0.3% fiber content, leading to a 14.17% increase compared to the control mix. Additionally, split tensile strength improved by 40.63% at 0.2% fiber content and by 65.68% at 0.3% fiber content. Although the slump decreased by 14% to 57% with increased fiber content, no bleeding or segregation was observed in any of the mixes. These findings underscore the potential of polyester fiber to improve the performance of high strength concrete in structural applications.